Análisis del uso de los Recursos Educativos Digitales del portal web del Ministerio de Educación del Ecuador denominado Oportunidades curriculares de Educación Integral Sexual por los docentes de la Unidad Educativa Fiscomisional Corazón de María en el año lectivo 2023-2024 - Belisaca Carrión, Jhon Enrique (2025)
Digital Educational Resources are fundamental and essential for education, allowing students to work at their own pace, achieving meaningful and individualized learning, while encouraging autonomy and responsibility in their learning process. This Curricular Integration Work analyzes the use of the Curricular Opportunities Digital Educational Resources in Integral Sexual Education of the Ministry of Education of Ecuador by the teaching staff at the Corazón de María Fiscomisional Educational Unit during the period 2023-2024. The present research is framed in a deductive method, with a quantitative approach and a descriptive non-experimental design. The specific population corresponds to the 21 teachers who are all the academic staff, who teach at the levels and sublevels, Initial II, General Basic Education and General Unified High School. For data collection, a questionnaire was designed and adapted from Orecchia (2020) and from the RED portal established by the Ministry of Education of Ecuador (2023) called Recursos Educativos Digitales de Oportunidades Curriculares para Educación Integral Sexual, data collection was done through the application of a structured survey, which was structured by dichotomous and questions on a Likert scale. The data collected were organized and analyzed using descriptive statistics, which allowed a diagnosis highlighting the occasionally use of the 10 Digital Educational Resources analyzed